A Taxonomic Service for Species Identification - Fuentes, Daniel; Fiore, Nicola (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2014)
Taxonomy is the science of discovering, classifying and categorizing organisms into groups. Names are given to species when they are recognized for ecology, potential hazards or just for human culture and admiration. However, current problems such as the high diversity of species, the hundreds of publications in which species are described and the lack of a single authoritative world register routine for the definition of the taxa cause frequent confusion in the taxonomy identification. In this paper, we propose a method to automatically extract, integrate and represent species taxonomy information from the main relevant biodiversity catalogues for its comparison and studio. Consequently, the time for information analysis is reduced and taxonomic nomenclature errors are avoided, which are essential for some biology areas of knowledge.